Maternal and perinatal outcome in cholestasis of pregnancy: a study in tertiary care hospital in North India - Kant, Anita; Goswami, Shivani; Gupta, Usha; Razdan, Amrita; Amle, Dnyanesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Intrahepatic cholestasis of pregnancy (IHCP) is the most common pregnancy related liver disorder. It typically presents with troublesome itching and can lead to complications for both mother and fetus. Thus, authors aimed to assess risk factors associated with IHCP as well as maternal and fetal outcome in pregnancy associated with IHCP in north Indian population. Methods: This hospital based analytical observational case control study enrolled 44 subjects with IHCP and 44 normal healthy pregnant controls. The subjects were assessed for demographic parameters, obstetric history, liver function tests including Bile acids. Outcome was measured as various parameters related to delivery and maternal and fetal complications. Results: Study groups were matched for age (0.52). Frequency of primipara was higher in IHCP (p=0.01). Serum bilirubin (p=0.002), liver enzymes (p<0.0001 for all) and Bile acids (p=0.001) were significantly elevated in IHCP subjects compared to controls. Further, frequency of preterm birth was higher in IHCP (p=0.013). Fetal complications (p=0.01) and birth weight (p=0.03) were higher in IHCP subjects. Conclusions: IHCP is associated with higher risk of complications in infants and to lesser extent in mothers.